AEROBIC INTERVAL EXERCISES VERSUS DIETARY CONTROL INDUCED CHANGES OF ADIPOKINES LEVELS, LIPID PROFILE AND QUALITY OF LIFE IN OVERWEIGHT OR OBESE CHILDREN (International Journal of Physiotherapy, 2016)
Background: Lately, childhood obesity has gained more attention. The present study constructed to compare the effectiveness of aerobic interval exercises and dietary control on plasma adipokines level, lipid profile and the health-related quality of life in overweight or obese children.Methods: Thirty-seven overweight or obese children at the age from 10-18 years were recruited and randomly classified into aerobic interval exercises (AIE) and dietary control (DC) groups. The Training load for AIE group was eight weeks of an intermittent short high intense burst of exercises throughout a regular training program primarily consisted of treadmill training. Whereas, subjects in the DC group were engaged in a balanced dietary plan. Plasma adipokines, lipid profile, and the health-related quality of life were assessed before and after the intervention.Results: Both groups were similar at the baseline (p>0.05). Within the AIE group; leptin, adiponectin and all lipid profile measures significantly changed (p